PENINGKATAN LITERASI PAJAK DAN PENDAMPINGAN PENDAFTARAN NPWP PRIBADI SECARA ONLINE DI DESA RIDOMANAH - Kania, Nina; Indra Tama, Annafi; Rahmawati, Rafika (An-Nizam, 2024)
As good Indonesian citizens, we have an obligation to contribute to the development of the country. One of the ways we contribute is by setting aside a portion of our income to pay taxes. Taxes are one of the largest sources of revenue for the country. To be able to make tax payments, each individual needs a Nomor Pokok Wajib Pajak (NPWP). Based on Article 1 Number 6 of Law Number 28 of 2007, NPWP is a taxpayer's identity card issued by the Direktorat Jenderal Pajak (DJP). Ridomanah Village is experiencing difficulties in terms of tax literacy and ownership of Nomor Pokok Wajib Pajak (NPWP) due to the low public understanding of tax obligations. To overcome this, the community service program is carried out by socialization and direct assistance methods in online NPWP registration. This activity began with observations and interviews to identify the obstacles faced by residents, followed by socialization about the importance of having an NPWP and tax obligations. After that, residents are accompanied in the online NPWP registration process. This program is expected to increase tax literacy, facilitate access to tax services, and assist the residents of Ridomanah Village in fulfilling their tax obligations in an effective and efficient way.